Survival rate and growth performance of molly fish (Poecilia latipinna) with ascorbic acid enrichment in Moina sp. - Rio Yusufi Subhan; Linuwih Aluh Prastiti (Arwana: Jurnal Ilmiah Program Studi Perairan, 2025)
Snow white molly (Poecilia latipinna, Lesueur 1821) is a popular ornamental freshwater fish introduced for aquarium use. This study aimed to evaluate the survival rate and growth performance of snow white molly fed Moina sp. enriched with ascorbic acid. The experimental design used was a Completely Randomized Design (CRD) with three treatments and three replicates: enrichment of Moina sp. with ascorbic acid at concentrations of (A) 150 mg/L, (B) 175 mg/L, and (C) 200 mg/L. The enriched Moina sp. was fed to snow white molly for a 30-day rearing period. The results showed that treatment B, with Moina sp. enriched at 175 mg/L of ascorbic acid, yielded the best outcomes: a survival rate of 86,66±5,7%, an absolute length of 2,5±0,1 cm/fish, and a specific growth rate of 4,02±0,32%/day. Based on these research, the 175 mg/L ascorbic acid enrichment dosage (treatment B) was significantly more effective in improving the survival and growth performance of snow white molly compared to other treatments.